The Teachers’ Strategy of Islamic Religious Education in Instilling the Character of Peace and Love at State Junior High Schools 22 Bandar Lampung - Efta Afriliani; Imam Syafe’I; Agus Jatmiko (Bulletin of Science Education, 2024)
The article analyze of the teachers’ strategy of islamic religious education in instilling the character of peace and love at state junior high schools 22 bandar lampung. The teacher uses qualitative descriptive that conducted at State Junior High School 22 Bandar Lampung. The result showed that the strategy applied by educators in cultivating a peace-loving character is using role model strategies, habituation and classroom conditioning. The peace-loving character that has been instilled; (1) working in groups; (2) share with friends; (3) respect other people's opinions; (4) empathy for others; (5) don't want to win alone; (6) likes to discuss; (7) doesn't like making a fuss or bothering other people; (8) likes to help other people; (9) able to intervene when someone is fighting; (10) interact well according to the norms that apply to peers and even adults.